PENERAPAN LATIHAN BERCAKAP-CAKAP PADA PASIEN HALUSINASI PENDENGARAN DI PUSKESMAS CIGEUREUNG KOTA TASIKMALAYA - Pratiwi, Novi Dini; Riyana, Asep; Maulana, Heri Dj (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2024)
Hallucinations are a symptom of a mental disorder where the concentration of the patient's mind is affected, it is difficult to think clearly and has difficulty controlling his emotions. While auditory hallucinations are hearing voice that speak, mock, order to do somothing that is sometimes dangerous. The purpose of this case study research is to describe the characteristics of patients, describe conversational practice, describe a decrease in signs and symptoms in patients with auditory hallucinations. This type of rich-writing design is descriptive using a case study report, the research process was carried out for 5 days. The results of the case study in this study showed that there was a decrease in the signs of symptoms in patients with auditory hallucinations, after implementing the strategy of implementing conversational exercises. The conclusion of this case study research is that the strategy of implementing conversational exercises in these two patients is effective in reducing the signs of hallucination symptoms and increasing the patient's ability to control their hallucinations.